Perceptions of teachers and students about the use of ICTs in physical education classes: uses, advantages, and projections - Alexis Matheu Pérez; Marcelo Muñoz; Manuel Cortés Cortés; Luis Díaz Contreras; Sergio Muñoz Sepúlveda; Paola Juica Martínez; Macarena Dehnhardt (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The digitalization of societies is not a homogeneous or mechanistic process that moves in parallel to technological processes, since the uses of ICT are linked to the social and political contingency of each country. Consequently, this paper set out to analyze the perception of teachers and students about the use of ICTs in Physical Education classes in schools in Santiago of Chile. The use of ICTs in Physical Education is uncommon in Chile, these are focused on physical exercise and folklore teaching. A qualitative methodology was used. Based on structured interviews with teachers and students from schools in the southern area of Santiago. These were analyzed through Atlasti software. A qualitative analysis of content and a thematic analysis was carried out through data coding. The results show that there are differences in the perception of ICT by teachers and students. The former prioritize technologies applied to physical exercise. The latter consider that technologies are important for obtaining information and managing communication between teacher and student. It is concluded that it is necessary to generate institutional mechanisms that allow socialization in new skills and knowledge of technologies, since the lack of training in these skills could produce severe problems in the integration into the new digital society that is developing in Chile. Likewise, there is a generational gap in the use of this type of technologies, which would affect the older population.